Susceptibility vessel sign on T2*-weighted gradient echo imaging in lacunar infarction - Al-Zghloul, Mansour; Wenz, Holger; Maros, Máté E.; Böhme, Johannes; Groden, Christoph; Förster, Alex (In vivo, 2018)
Background/Aim: In stroke due to large vessel occlusion, thrombotic material can be demonstrated by the susceptibility vessel sign (SVS), a hypointense signal on T2*-weighted gradient echo magnetic resonance (GRE) images. In the present study, we evaluated the value of GRE for the detection of perforating artery occlusion in hyperacute lacunar infarction (LI). Materials and Methods: The presence of SVS on GRE in 58 patients with LI who underwent magnetic resonance imaging within 24 hours after symptom onset was analyzed. Results: On diffusion-weighted images (DWI), LI was found in the basal ganglia in 17.2%, internal capsule in 25.9%, corona radiata in 19.0%, thalamus in 32.8%, and brainstem in 5.2%. On GRE a subtle circumscribed hypointense signal at the lower edge of the LI consistent with SVS was detected in 11/58 (19%) patients. Patients with SVS had larger ischemic lesions on DWI (p=0.045). Conclusion: SVS on GRE may be useful for detection of perforating artery occlusion in a subset of patients with hyperacute LI.
Gesehen am 15.12.2020